Effect of an Electronic Module Based on Project-Based Learning Integrated with Local Wisdom on Students’ Critical Thinking Skills - Jaziroh Dwi Ningsih; Raudhatul Jannah; Dewi Juita (Journal of Innovative Physics Teaching, 2026)
In the 21st century, critical thinking skills are regarded as essential competencies that every student must develop, particularly in physics. However, preliminary test results indicate that students’ critical thinking skills remain low, with an average score of 61.77%. This study examined the effect of an electronic module (e-module) based on Project-Based Learning (PjBL) integrated with local wisdom on students’ critical thinking skills, compared to learning using the Independent Curriculum textbook and PjBL-based worksheets. This study employed a quantitative approach with a quasi-experimental design using a Posttest-Only Control Group Design. The research sample comprised 32 students in the experimental class (F2.4) and 30 students in the control class (F2.3). Data analysis included normality tests, homogeneity tests, and an independent samples t-test. The results showed that the mean critical thinking score of the experimental class (M = 87.97) was significantly higher than that of the control class (M = 72.58), with a mean difference of 15.39 points. Statistical analysis confirmed a significant effect: t(60) = 8.581, p = 0.000 (< 0.05). Effect size analysis using Cohen’s d yielded d = 1.7, indicating a very large practical significance. It is therefore concluded that the PjBL-based e-module integrated with local wisdom has a significant and practically meaningful effect on students’ critical thinking skills compared to the conventional learning approach